Jesus' blood and righteousness Paul's theology of imputation - Vickers, Brian J. 1966- (Wheaton, IL Crossway, 2006)
Includes bibliographical references and index.
Keywords: Righteousness (Christian theology).; Bible. N.T. Epistles of Paul -- theology